Corak Tafsir dalam Islam: Analisis Metode Tematik, Maudhu’i, dan Tahlili - Zumrotun Nafisah; Eni Damayanti; Azka Naja; Ana Rahmawati (Jurnal Ilmiah Al-Furqan: Al-qur’an Bahasa dan Seni, 2024)
This article presents a comparative analysis of different methods and styles of interpreting the Qur’an. By comparing the works of classical and contemporary commentators, this article aims to reveal how each method provides different interpretations. The research method used is library research. Research results The development of methods for interpreting the Qur’an has occurred since the time of the Prophet Muhammad until now, influenced by the work of Western scientists which have been translated into Arabic. Shifts in the interpretation of the Koran were influenced by social changes in society, while Islam began to experience modernization in the 19th century. In Indonesia, Muslim scientists are also actively translating the Koran into Indonesian. There are various ways of interpreting the Koran that support understanding of the holy book. In conclusion, choosing the right interpretation method is very important to produce an interpretation of the Qur’an that is relevant to the social and cultural context and can provide solutions to the problems of the people.